Pengaruh Injil dalam adat Batak : pendekatan praktisi - Pasaribu, John B. (John Bidel), 1942- (Jakarta : Papas Sinar Sinanti, 2002)
Influence of Christian values on Batak ethnic group traditional belief
Includes bibliographical references (p. 115-116)
Keywords: Batak (Indonesian people) -- Religion; Christians; Christian ethnics -- Indonesia; Batak (Indonesia people)